46 Dietetic intervention for patients with advanced chronic kidney disease – a conservative management approach. (13th October 2019) - Yokum, Dawn; Go, Jaryn; Tayab, Ruby; White, William; Yaqoob, Magdi
Abstract : Conservative management (supportive care) is defined as individuals with advanced chronic kidney disease (CKD) who choose not to undergo dialysis (supported by their kidney team). A renal supportive care (SC) outpatient service has existed for over 10 years at this large renal unit. Dietetic management in this population is complex, with the aim being to alleviate and/or reduce the risk of symptoms associated with advanced CKD and support quality of life. This may involve dietetic interventions such as: management of blood biochemistry (potassium, phosphate and mineral bone disease), fluid status (no added salt), low protein and nutritional support. The aim is to evaluate current dietetic practice using a snapshot of the SC population The method used was a random sample of selected patients. Data collected included demographics, prevalence of abnormal blood results, low protein diet advice and nutritional support. The results for twenty patients (11% of the SC population) were used. Median age 80.5, range: 70 – 99years). Median duration under SC service: 23.5 (range: <1–56) months Eighteen patients (90%) had received dietetic input. Half of these patients (n=9) required a low protein diet and 33% (n=6) were given nutritional supplementation. Three patients (15%) had either a recent elevated blood potassium or phosphate level. In conclusion, the complexity of dietetic management in this SC patient population highlights the importance of a renal dietitian's involvement to help alleviate symptoms of advanced CKD and support quality of life. Further research into outcomes including patient/carer experience surveys is warranted.